ChemInform Abstract: Solid Solution Pb1‐xEuxTe: Constitution and Thermoelectric Behavior. Issue 45 (October 2016) - Wang, Xin‐Ke; Veremchuk, Igor; Bobnar, Matej; Zhao, Jing‐Tai; Grin, Yuri
Abstract: Polycrystalline Pb1‐x Eux Te samples (x = 0—0.5) are prepared by melting stoichiometric amounts of the elements (graphite‐coated evacuated silica tubes, 1273 K, 6 h) followed by spark plasma sintering of the pelletized product (673 K, 60 MPa, 7 min).